2020
DOI: 10.3390/pr8111457
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Selected Physicochemical Properties of Commercial Apple Juices

Abstract: The paper presents the comparison of quality of six different commercial apple juices produced in Poland. The apple juices came from two different Polish companies. From each manufacturer three various juices were selected: two cloudy and clarified one produced as a mixture of different apple varieties. The following properties were evaluated: density, soluble solid content, viscosity, total phenolic contents, phenolic acid, and antiradical activity. The obtained results showed that three from fourth cloudy ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(50 reference statements)
5
8
0
1
Order By: Relevance
“…Active acidity was determined by pH measurements at ambient temperature using laboratory pH meter Fisher Scientific ACCUMET Bio Set AE150 (Fisher, Waltham, MA, USA). For each sample, a 10 mL volume of apple extract was measured, the pH electrode was inserted, and after stabilization, the pH value was displayed on the pH meter screen [34].…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…Active acidity was determined by pH measurements at ambient temperature using laboratory pH meter Fisher Scientific ACCUMET Bio Set AE150 (Fisher, Waltham, MA, USA). For each sample, a 10 mL volume of apple extract was measured, the pH electrode was inserted, and after stabilization, the pH value was displayed on the pH meter screen [34].…”
Section: Physico-chemical Analysismentioning
confidence: 99%
“…All extract were filtered through a 0.20 µm syringe filter (Nylon, Macherey–Nagel, Düren, Germany), and 20 µL of the sample was injected in the system in triplicate. The separation was carried out using a Bionacom Velocity STR (3.0 mm × 250 mm, 5.0 µm) column at 25 °C 40 .…”
Section: Methodsmentioning
confidence: 99%
“…The peaks of the compounds were identified and quantified by comparison of the retention times and spectra of the samples with calibration curves that had been previously prepared with standards. The runs were monitored at 260 nm 40 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candrawinata et al (2012) concluded that the clarification process of apple juice minimized its phenolic content and its antioxidant activity and that the cloudy variety is richer in antioxidant activity and may be used in the food industry. Rydzak et al (2020) demonstrated that commercial cloudy apple juice had a total phenolic content three times higher than clear apple juices. ABTS: 2,2 0 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid an antioxidant activity assay.…”
Section: Total Phenolic Contents Total Flavonoid Contents and Antioxidant Activity Of The Supplemented Juicesmentioning
confidence: 99%